2012
DOI: 10.1016/j.chembiol.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Stimulates Macropinocytosis: Implications for Cellular Uptake of Arginine-Rich Cell-Penetrating Peptides and HIV

Abstract: CXCR4 is a coreceptor of HIV-1 infection in host cells. Through a photocrosslinking study to identify receptors involved in internalization of oligoarginine cell-penetrating peptides (CPPs), we found that CXCR4 serves as a receptor that stimulates macropinocytic uptake of the arginine 12-mer peptide (R12) but not of the 8-mer. We also found that stimulating CXCR4 with its intrinsic ligands, stromal cell-derived factor 1α and HIV-1 envelope glycoprotein 120, induced macropinocytosis. R12 had activity to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 48 publications
4
97
0
Order By: Relevance
“…5). Hep3B cells were resistant to the action of these inhibitors and CXCR4 internalization was blocked by DMA, an inhibitor of macropinocytosis [37] that specifically blocks SDF-1α induced internalization of CXCR4 (Fig. 6), but not other membrane receptors (Suppl.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5). Hep3B cells were resistant to the action of these inhibitors and CXCR4 internalization was blocked by DMA, an inhibitor of macropinocytosis [37] that specifically blocks SDF-1α induced internalization of CXCR4 (Fig. 6), but not other membrane receptors (Suppl.…”
Section: Discussionmentioning
confidence: 98%
“…It has been recently reported that CXCR4 could also be internalized by macropinocytosis. Therefore, we treated Hep3B cells with dimethylamiloride (DMA), which is an inhibitor of this internalization pathway [37]. As shown in Fig.…”
Section: Sdf-1α Induces the Internalization Of Cxcr4mentioning
confidence: 99%
“…Endocytosis is a generic term for several different processes, such as phagocytosis for large particles and pinocytosis for smaller ones, as well as receptor-mediated endocytosis in which clathrin or caveolin pits are involved (Madani et al, 2011). Several receptors were uncovered to be involved in internalization of CPPs, such as chemokine receptors (Tanaka et al, 2012), syndecans (Letoha et al, 2010), neuropilins (Prud'homme and Glinka, 2012), the family of integrins (Mokhtarieh et al, 2013), homing sequences, and positively-charged scavenger receptors (Reissmann, 2014). Micropinocytosis appears to be a pathway for the MCoTI-II peptide to enter into the cell.…”
Section: Translocation Of Cpps Into Cellsmentioning
confidence: 99%
“…15) Furthermore, a membrane-associated chemokine receptor CXCR4 is proposed to serve as a cell-surface receptor responsible for internalization of dodeca-arginine (R12) via macropinocytosis. 16) On the other hand, there is also strong evidence that other classes of endocytosis pathways such as clathrin-mediated endocytosis [17][18][19] and caveolae-mediated endocytosis 20,21) are involved in internalization of these peptides. It is noted that internalization modes of arginine-rich CPPs can be strongly affected by variable factors in each experiment, such as the physicochemical natures of peptides, cell types, incubation temperatures and cargoes to be delivered, which makes mechanistic studies on their internalization exceptionally difficult.…”
Section: Introductionmentioning
confidence: 99%